The Poverty Impacts of Cash and In-Kind Transfers : Experimental Evidence from Rural Mexico - Skoufias, Emmanuel; Unar, Mishel; González-Cossío, Teresa (Taylor and Francis, 2013)
The unique experimental design of the Food Support Programme (Programa de Apoyo Alimentario) is used to analyse in-kind and cash transfers in the poor rural areas of southern states of Mexico. The intent-to-treat effect on poverty of cash transfers of real value 25 per cent less than the market value of in-kind transfers is identical to that of in-kind transfers. Potential explanations of this result are investigated by looking into the differences in impacts of in-kind and cash transfers on food consumption and non-food expenditures and on the allocation of family labour between agricultural and non-agricultural activities. Both in-kind and cash transfers have identically large positive impacts on food consumption. Non-food expenditures are also higher in the localities with cash transfers, whereas they remain unaffected in the localities with in-kind transfers. Both kinds of transfers have a significant impact on the time allocation of males (and not females) who switch from agricultural to non-agricultural activities. But, the availability of cash transfers has a significantly higher marginal effect than in-kind transfers on the shift towards non-agricultural activities. Overall, the findings suggest that cash transfers may be better able than in-kind transfers at mitigating the impact of market imperfections, thus increasing both equity and efficiency.